Urban forestry: Sustainable option for environmental conservation in Nigeria (2001)
This paper examined the roles of trees/forests in urban environmental conservation: Environmental benefits were highlighted, they encompass landscape enhancement, recreation, education and general well-being, a habitat for wildlife; climatic modification, air and noise pollution control, erosion control, catchment area protection for urban water sup/ lie and the productive use or safe disposal of urban wastes. Prequisite determinants of sustainable urban forestry development were also identified to include technical, financial, human and institutional resources. The need to integrate ecological principles into the physical and social fabrics of urban landscape planning was stressed vis-a-vis Nigeria where land economic and technological development limit the provision and enforcement of environmental conservation measures.